2D High‐Entropy Hydrotalcites. Issue 45 (27th September 2021) - Yu, Xiwen; Wang, Bing; Wang, Cheng; Zhuang, Chen; Yao, Yingfang; Li, Zhaosheng; Wu, Congping; Feng, Jianyong; Zou, Zhigang
Abstract: High‐entropy materials (HEMs) with unique configuration and physicochemical properties have attracted intensive research interest. However, 2D HEMs have not been reported yet. To find out unique properties of combining 2D materials and HEMs, a series of 2D high‐entropy hydrotalcites (HEHs) is created by coprecipitation method, including quinary, septenary, and even novenary metallic elements. It is found that the fast synthetic kinetics of coprecipitation process conquers the thermodynamically solubility limitation of different elements, which is the prerequisite condition to form HEHs. As the oxygen evolution reaction (OER) electrocatalysts, HEHs show significantly decreased apparent activation energy compared with low‐entropy hydrotalcites (LEHs) due to the lattice distortion induced by the multimetallic character of HEHs. This work opens up a new avenue for the development of 2D HEMs, which broadens the family of HEMs and presents a most promising platform for exploring the unknown properties of HEMs. Abstract : High‐entropy hydrotalcites have been obtained which exhibit superior electrocatalytic performance of oxygen evolution reaction due to the combination of both the dimensional confinement and the high‐entropy effects. This study has opened up a dictionary of 2D high‐entropy material group and provided a versatile and flexible material platform for a wild range of fields.